(untitled) (Research, Society and Development, 2021)
Brazilian sheep farming represents an important segment within the national livestock industry, generating employment and income along the production chain. Within this segment, sheep milk production is still incipient in Brazil, but it has great potential due to the ability to add value to the product through the production of derivatives, appreciated in different consumer markets. The aim of this study was to evaluate the milk production of Texel sheep, managed in a native field and supplemented. 17 adult sheep were used, managed in a native field receiving 1% commercial feed containing 14% crude protein. The ewes were milked on two occasions during the lactation period, with the aid of a mechanical milker and prior administration of oxytocin. Nutritional management allowed the maintenance of the body condition score. Dairy production was considerable for the breed standard, which does not represent a dairy biotype. The study allows us to infer that there is potential for using the Texel breed in sheep milk production systems.